The Effect of Aging on Pacing Strategies in Short and Long Distance Duathlon. Issue 3 (27th May 2019) - Nikolaidis, Pantelis T.; Villiger, Elias; Victor Sousa, Caio; Rosemann, Thomas; Knechtle, Beat
ABSTRACT: Background/Study context : Many studies have been conducted on the triathlon during the last several years; however, less information exists with regards to duathlon ( i.e ., Run 1, Bike and Run 2). The aim of the present study was to examine the effect of age on pacing ( i.e ., the relative contribution – % – of each discipline and transition times – Transition 1 and Transition 2 – to overall race time) of duathletes competing either to short ( i.e ., 10 km Run 1, 50 km Bike and 5 km Run 2) or long distance ( i.e ., 10 km Run 1, 150 km Bike and 30 km Run 2). Methods : We analyzed 6, 671 finishes (women's, n = 1, 037, age 36.6 ± 9.1 years; men's, n = 5, 634, 40.0 ± 10.0 years) of 3, 881 duathletes competing in 'Powerman Zofingen', the World Championship, from 2003 to 2017, in both the short and the long distance race. Results : A large discipline×distance interaction on relative time (%) was observed in the short distance (p < .001, η 2 p = .936); 24.7%, 57.4%, and 15.8% were spent in Run 1, Bike, and Run 2, respectively. In the long distance, the relative contribution of disciplines was 8.0%, 59.0%, and 32.1%, respectively. A trivial discipline×sex interaction on relative time (%) was shown in the short (p < .001, η 2 p = .007) and long distance (p < .001, η 2 p = .016). In the short distance, a small discipline×age group interaction on relative time (%) was found (p < .001, η 2 p = .030) with younger age groups spending less time (%) in Run 1, Transition 1 and Transition 2, and older groups less time (%) in Bike and Run 2. In the long distance, a moderate discipline×age group interaction on relative time (%) was observed (p < .001, η 2 p = .077) with younger age groups spending less time (%) in Run 1, Transition 1, Transition 2 and Run 2, and older groups less time (%) in Bike. Conclusions : These findings suggest that younger duathletes are relatively faster in Run 1 and transitions, and older duathletes in Bike in both distances. However, older duathletes are relatively faster in Run 2 in the short distance and younger duathletes are relatively faster in Run 2 in the long distance. The magnitude of the combined effect of discipline and age group on pacing was larger in the long than in the short distance. Therefore, athletes and coaches should be aware of the variation of pacing by age group and distance of a duathlon race such as 'Powerman Zofingen'.